2016
DOI: 10.1155/2016/5093870
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Experimental Model to Evaluate Analgesic Effect of Remote Ischemic Preconditioning in Acute Postoperative Pain

Abstract: This study aims to evaluate the viability of a clinical model of remote ischemic preconditioning (RIPC) and its analgesic effects. It is a prospective study with twenty (20) patients randomly divided into two groups: control group and RIPC group. The opioid analgesics consumption in the postoperative period, the presence of secondary mechanical hyperalgesia, the scores of postoperative pain by visual analog scale, and the plasma levels interleukins (IL-6) were evaluated. The tourniquet applying after spinal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…To date, little work has investigated the use of an IPC protocol on reducing sensitivity to a purposely introduced painful stimulus in healthy individuals. Previous literature, however, has investigated the analgesic effect of IPC in a clinical setting, indicating that postoperative pain intensity (Memtsoudis et al, 2010;Pereira et al, 2016) morphine use (Memtsoudis et al, 2010), and mean hospital stay (Pereira et al, 2016) can be reduced in patients who undergo IPC before a surgical procedure. In like manner, the current study found that IPC can modulate pain sensitivity by reducing total time under pain; in contrast, however, absolute pain intensity was not affected.…”
Section: Ipc Pain Modulationmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, little work has investigated the use of an IPC protocol on reducing sensitivity to a purposely introduced painful stimulus in healthy individuals. Previous literature, however, has investigated the analgesic effect of IPC in a clinical setting, indicating that postoperative pain intensity (Memtsoudis et al, 2010;Pereira et al, 2016) morphine use (Memtsoudis et al, 2010), and mean hospital stay (Pereira et al, 2016) can be reduced in patients who undergo IPC before a surgical procedure. In like manner, the current study found that IPC can modulate pain sensitivity by reducing total time under pain; in contrast, however, absolute pain intensity was not affected.…”
Section: Ipc Pain Modulationmentioning
confidence: 99%
“…In like manner, the current study found that IPC can modulate pain sensitivity by reducing total time under pain; in contrast, however, absolute pain intensity was not affected. It should be pointed-out that previous clinical research (Memtsoudis et al, 2010;Pereira et al, 2016) evaluated pain intensity in the recovery from a painful stimulus, while the current study evaluated pain intensity during the administration of the painful stimulus and not after its removal. Therefore, it remains possible that IPC can reduce pain intensity during withdrawal of a painful stimulus in young, healthy individuals, and should be considered by future research.…”
Section: Ipc Pain Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of a tourniquet alone in cyclic fashion may also induce hypoalgesia. Cyclic restriction of limb blood flow has been shown to reduce pain following surgery, when applied both post-operatively [113] and perioperatively [114]. Moreover, cyclic application of BFR following an acute bout of muscle damage inducing exercise has been shown to reduce muscle soreness [115].…”
Section: Bfr Exercise and Hypoalgesiamentioning
confidence: 99%
“…For example, pain level is one of the major factors used in the triage and acuity scale for emergency department to screen life-threatening patients [14,15]. Assessing pain also helps evaluate the effect of analgesia on postoperative, endodontic and multiple treatments [16,17] and is essential in improving quality of healthcare [18]. Currently, the clinical gold standard in pain assessment is done via individual's self-reported numerical scale.…”
Section: Introductionmentioning
confidence: 99%